WORKING MEMORY, SYNTA, AND ATTENTION: PSYCHOLINGUISTICS INSIGH INTO COGNITIVE LOAD DURING SENTENCE PROCESSING - Desry Nurliana; Telaumbanua, Adrian Prasetya; Muhammad Faiz; Lubis, Yani (Linguistics and Literature Journal, 2025)
This study investigates how cognitive load affects learners’ sentence processing during English learning, focusing on junior high school students in Medan, Indonesia. Using a qualitative descriptive design within a psycholinguistic framework, data were collected through classroom observations, sentence-based comprehension tasks, and semi-structured interviews with twelve eighth-grade students. The findings revealed that students experienced notable cognitive strain when processing long or syntactically complex English sentences, often manifested through hesitation, rereading, and verbal confusion. Three key aspects emerged: working memory limitation, syntactic complexity awareness, and attention management. Learners with limited working memory struggled to maintain meaning across lengthy sentences, while those with higher syntactic awareness managed complexity more effectively through chunking or focusing on key structures. Attention fluctuations were also observed, influencing comprehension consistency. The study concludes that sentence processing in EFL contexts is shaped by the interaction of cognitive capacity, grammatical understanding, and attentional control. Pedagogically, the findings suggest that English teachers should design learning tasks that minimize unnecessary cognitive load while fostering metacognitive awareness and self-regulation in sentence comprehension. Keywords: attention management, cognitive load, EFL learners, psycholinguistics, sentence processing, working memory, syntactic awareness